The study of Anhui University campus network architecture: migration to a scalable network - Zhou, Haoxue (2022)
Anhui University is a key construction University of the national "211" project, with a long history and profound culture. The school now has four campuses and a university science and Technology Park, with a construction area of 1.25 million square meters 28000 students, including about 6000 graduate students and 21500 full. There are about time undergraduate and junior college students. Due to the problems of network planning in Longhe campus and Qingyuan campus, it is necessary to re plan the network arc hitecture of the two campuses to ensure the redundancy of the network architecture and meet the needs of all aspects of the campus users. The campus network is a computer network based on modern network technology, multimedia technology and new technology, as a computer network connecting the campus internal teaching building, laboratory building, dormitory area and other campus intranets, and as a carrier connecting the campus intranet and the extranet, providing a good network operation environment for the comprehensive use of teaching, management, and information sharing between multiple campuses. At present, most colleges and universities in our country have implemented multi campus teaching. With the emergence of many new educational means, such as distance teaching, video conference system and so on, these highefficiency teaching methods have higher requirements for the campus network. They not only realize cross regional campus resource sharing, improve the quality of teaching, but also adapt to the later development and expansion of the network. Campus network is a typical representative of local area network. Through the network, the communication between Longhe campus and Qingyuan campus of Anhui University is realized, and the resource sharing and information exchange between the two campuses are convenient. With the increasing demand for multi campus network in Colleges and universities, the requirements for network planning in multi campus are more stringent, more network functions need to be realized, and more technologies need to be implemented. Therefore, the pre planning and design of multi campus is very important, which is the premise of the final network structure, which will directly affect the survival time of campus network, As well as the workload of late expansion, good early network planning, will determine the late development limitations of a network structure. Campus network is to promote quality education and meet the needs of the knowledge age. In view of these problems, the network planning of Anhui University in the early stage has been unable to keep up with the speed of network development, so this topic is to carry out network planning and design according to the current network ne eds of Anhui University.